Combination chemotherapy with cisplatin, etoposide and irinotecan in patients with extensive small-cell lung cancer: A phase II study of the Hellenic Co-operative Oncology Group - Pectasides, D.; Samantas, E.; Fountzilas, G.; Briasoulis, E.; Kosmidis, P.; Skarlos, D.; Dimopoulos, M.A.; Kalofonos, H.P.; Economopoulos, T.; Syrigos, K. (Lung Cancer, 2007)
Objective: The purpose of this study was to evaluate the efficacy and toxicity of cisplatin, etoposide and irinotecan as first-line treatment in patients with extensive small-cell lung cancer (E-SCLC). Patients and methods: Chemo-naïve adult patients with a performance status (PS) of 0-2 and adequate organ function were eligible. Patients received cisplatin 20 mg/m2 i.v. daily for three consecutive days, etoposide 75 mg/m2 i.v. daily for three consecutive days and irinotecan 120 mg/m2 i.v. on day 2, every 21 days for six to eight cycles. Administration of G-CSF was given in the presence of febrile neutropenia and as a 5-day prophylaxis around the recorded nadir day in patients who developed grades 3-4 neutropenia. Results: Fifty-six patients were assessable. The median age was 62.2 years; 96.4% had PS 0-1, 33.5% had >3 metastatic sites. The overall response rate was 80.4% with 8 (14.3%) patients achieving a complete response. The median time to tumor progression was 7.8 months [95% confidence interval (CI), 7.1-8.6 months] with a median survival of 15.1 months [95% CI, 9.7-20.5 months] and 1-year survival rate of 56.5%. One patient died from toxicity. Grades 3-4 neutropenia occurred in 37.5% of patients, grades 3-4 thrombocytopenia occurred in 10.9% of patients and 11 (19.6%) patients developed febrile neutropenia. Grades 3-4 non-hematological toxicities were primarily nausea-vomiting 3.6%, diarrhea 7.1% and fatigue 3.6%. Conclusion: This study strongly suggests that cisplatin, etoposide and irinotecan combination is very effective for the treatment of E-SCLC with good safety profile. The triplet regimen currently seems a promising regimen and has to be further explored in phase III trials. © 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cisplatin; Etoposide; Extensive small-cell lung cancer; Irinotecan